1980
DOI: 10.1113/jphysiol.1980.sp013271
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the release of adenosine from slices of rat cerebral cortex.

Abstract: 1. The characteristics of the release of adenosine have been examined from slices of rat cerebral cortex after incubation with [3H]adenine or [3H]adenosine. 2. Increasing the potassium concentration of the extracellular medium to 36 or 54 mM did not evoke any release, but release was observed in the first post‐potassium sample. This occurred whether potassium was present for 2 or 10 min. 3. Calcium‐free solutions or verapamil prevented the post‐potassium release of tritium. Tetraethylammonium bromide and 4‐ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

1981
1981
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 35 publications
(49 reference statements)
5
13
0
Order By: Relevance
“…The maximum efflux did not occur until 20 min after that of [3H]-noradrenaline efflux or contraction. The time course of 3H-purine efflux was nearly identical to that from the rat cerebral cortex slice described by Hollins & Stone (1980).…”
Section: Discusionsupporting
confidence: 73%
See 1 more Smart Citation
“…The maximum efflux did not occur until 20 min after that of [3H]-noradrenaline efflux or contraction. The time course of 3H-purine efflux was nearly identical to that from the rat cerebral cortex slice described by Hollins & Stone (1980).…”
Section: Discusionsupporting
confidence: 73%
“…At high concentrations, KCI evokes a Ca2+-dependent purine efflux from various tissues, e.g., guinea-pig cerebral cortical synaptosomes (White, 1978;Potter & White, 1980) and rabbit vascular 0007-1188/82/120625-05 $01.00 adrenergic nerves (Katsuragi & Su, 1980;1982). Hollins & Stone (1980) found that ouabain (10-4M) as well as KCI elicited a Ca2+-dependent efflux of 3H-purines from rat cerebral cortex slices. The present study was, therefore, designed to compare the releasing effects of ouabain and high KCI on noradrenaline and purines with particular reference to their origins.…”
Section: Introductionmentioning
confidence: 99%
“…The Ca2+ dependency of ouabain-evoked release has been described previously (Hollins & Stone, 1980b With tissue from Wistar rats, morphine at 1 and 10JAM caused a small but significant elevation of ouabain-evoked purine release (Table-2). At both concentrations this effect could be blocked by naloxone, 0.1 or 1 JM.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous examination of the characteristics of ouabain-evoked purine release was performed on tissue from rats only (Hollins & Stone 1980b) and it is possible that the properties of cortex slices important for ouabain-evoked release differ in rats and mice. We have concluded elsewhere that purine release by ouabain is probably not due to a simple inhibition of (Na+, K+) ATPase (Hollins, Stone & Lloyd, 1980;Stone, Hollins & Lloyd, 1981;.…”
Section: Discussionmentioning
confidence: 99%
“…Second, in CSD ATP is released extracellularly (Schock et al 2007), and this will be broken down to adenosine by ecto-ATPases. Third, in vivo CSD is thought to be initiated, at least in part, by elevated extracellular K ϩ (Vyskocil et al 1972), and K ϩ -induced depolarization also increases the extracellular adenosine concentration in various brain regions (Chen et al 1992;Van Wylen et al 1986) including cortex (Hollins and Stone 1980;Pazzagli et al 1994).…”
Section: Discussionmentioning
confidence: 99%